Effect of Zn substitution on the magnetic and magnetocaloric properties of Cd1−xZnxCr2Se4 spinel. Issue 6 (24th January 2017) - Bouhbou, M.; Moubah, R.; Belayachi, W.; Belayachi, A.; Lassri, H.
Abstract : The influence of Zn substitution on the magnetic and magnetocaloric properties of Cd1− x Zn x Cr2 Se4 (0.35 ≤ x ≤ 0.45) spinel was investigated. Abstract : The influence of Zn substitution on the magnetic and magnetocaloric properties of Cd1− x Zn x Cr2 Se4 (0.35 ≤ x ≤ 0.45) spinel was investigated. All the samples exhibited two successive magnetic transitions associated with the reentrant spin glass at a freezing temperature ( T f ) and Curie temperature ( T C ). It was demonstrated that T f changed slightly with the Zn content; however, the T C value decreased with increasing Zn content due to the decrease of lattice constant. The magnetic entropy variation (−Δ S M ) was found to exhibit two maxima at T C and T f, which have an opposite trend as a function of Zn content. With increasing Zn content, (−Δ S M ) was found to decrease at T C, whereas at T f, (−Δ S M ) increased. It was shown that the change of (−Δ S M ) is closely correlated to the local exponent factor n at both transitions. The results showed that materials with double magnetic transitions could be integrated in a new class of magnetic refrigeration working in different temperature windows.